2023
DOI: 10.17221/77/2022-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Apocrine cystomatosis: From the aspect of epithelial-mesenchymal transition

et al.

Abstract: Apocrine cystomatosis, also called epitrichial sweat gland cystomatosis, is a non-neoplastic condition characterised by multiple dilated cysts of sweat gland origin. Histopathologically, these cysts comprise two layers of cells: an inner layer of glandular epithelial cells and an outer layer of myoepithelial cells. A case of apocrine cystomatosis was admitted to a local hospital. The microscopic investigation revealed that some enlarged cysts showed the transition of glandular epithelial cells into a spindle, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…"Detecting the disease in the early stages is essential to halt progression. Over the past decade, significant advances have been reported in the diagnosis and management of keratoconus" [5].…”
Section: Discussionmentioning
confidence: 99%
“…"Detecting the disease in the early stages is essential to halt progression. Over the past decade, significant advances have been reported in the diagnosis and management of keratoconus" [5].…”
Section: Discussionmentioning
confidence: 99%
“…Focus on whether the patient has a history of lidocaine allergy, ischemic heart disease, high blood coagulation (lower limb venous thrombosis, cerebral infarction, etc. ), or hemorrhagic diseases, and whether the patient has used aspirin, Plavix (Clopidogrel Hydrogen Sulphate), warfarin, compound Danshen (Radix Salviae Miltiorrhizae) dripping pills, and other anticoagulants or Traditional Chinese Medicine for activating blood and resolving stasis over a long period [4]. Puncture can only be performed at least 7 days after correcting coagulation dysfunction or stopping anticoagulant drugs.…”
Section: Preparation Before Puncture 311 Inquire About Relevant Medic...mentioning
confidence: 99%
“…To guide physicians in the proper management of thyroid nodules, several international guidelines have been developed, and US-based risk stratification has been suggested to aid in deciding when to perform fine-needle aspiration (FNA) or recommend follow-up US for thyroid nodules [2][3][4][5][6][7][8][9]. Several studies have compared the diagnostic performance of various USbased risk stratification systems for diagnosing thyroid malignancies and revealed that the Korean Thyroid Imaging Reporting and Data System (K-TIRADS), proposed by the Korean Society of Thyroid Radiology/Korean Thyroid Association, had higher sensitivity than other systems [10][11][12][13][14]. Nonetheless, the studies also reported that the rate of unnecessary biopsies was higher in K-TIRADS, which had lower specificity [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have compared the diagnostic performance of various USbased risk stratification systems for diagnosing thyroid malignancies and revealed that the Korean Thyroid Imaging Reporting and Data System (K-TIRADS), proposed by the Korean Society of Thyroid Radiology/Korean Thyroid Association, had higher sensitivity than other systems [10][11][12][13][14]. Nonetheless, the studies also reported that the rate of unnecessary biopsies was higher in K-TIRADS, which had lower specificity [10][11][12][13][14][15]. As part of an effort to reduce unnecessary biopsies, some studies have simulated different size cutoffs for biopsies and revealed that the higher rate of unnecessary biopsies of K-TIRADS is attributed to the lower cutoff sizes for biopsies [11,16,17].…”
Section: Introductionmentioning
confidence: 99%